2020
DOI: 10.1007/s00384-020-03804-7
|View full text |Cite
|
Sign up to set email alerts
|

Lateral pelvic lymphadenectomy for low rectal cancer: a META-analysis of recurrence rates

Abstract: Background Locoregional recurrence (LR) remains a problem for patients with lower rectal cancer despite standardized surgery and improved neoadjuvant treatment regimens. Lateral pelvic lymph node dissection (LPLND) has been routine practice for some time in the Orient/East, but other regions have concerns about morbidity. As perioperative care and surgical approaches are refined, this has been revisited for selected patients. The question as to whether LPLND improves oncological outcomes was explored here. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…Some studies have shown reduced risk of local recurrence when LLND is performed, both in patients with or without MRI-suspected LLNM [9,24]. However, in a meta-analysis by Fahy et al no such benefit was observed [25]. Moreover, it has been suggested that LLND results in longer operative time, greater intraoperative blood loss, increase in postoperative complications and increased incidence of dysuria and impaired sexual functions without subsequent improvement of survival [26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown reduced risk of local recurrence when LLND is performed, both in patients with or without MRI-suspected LLNM [9,24]. However, in a meta-analysis by Fahy et al no such benefit was observed [25]. Moreover, it has been suggested that LLND results in longer operative time, greater intraoperative blood loss, increase in postoperative complications and increased incidence of dysuria and impaired sexual functions without subsequent improvement of survival [26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…Recently published meta‐analyses of retrospective and prospective studies and RCTs comparing the total mesorectal excision (TME) with prophylactic and therapeutic LPLND and the TME alone showed no differences in terms of survival and recurrence and greater postoperative complications, such as urinary and sexual dysfunction, in the TME with LPLND group. The results remained consistent in patients with or without neoadjuvant chemoradiotherapy 1–6 . On the other hand, long‐term follow‐up data from the JCOG0212 randomized clinical trial did not support the noninferiority of mesorectal excision (ME) alone compared with ME with LPLND in patients with stage II and III low rectal cancer who did not meet size‐based imaging criteria predictive of lateral pelvic lymph node (LPLN) metastasis; the cumulative local recurrence rate was significantly lower in the ME with LPLND group than in the ME group.…”
Section: Introductionmentioning
confidence: 95%
“…The results remained consistent in patients with or without neoadjuvant chemoradiotherapy. [1][2][3][4][5][6] On the other hand, long-term follow-up data from the JCOG0212 randomized clinical trial did not support the noninferiority of mesorectal excision (ME) alone compared with ME with LPLND in patients with stage II and III low rectal cancer who did not meet size-based imaging criteria predictive of lateral pelvic lymph node (LPLN) metastasis; the cumulative local recurrence rate was significantly lower in the ME with LPLND group than in the ME group. As the difference was mostly due to decreased lateral pelvic recurrences, the authors concluded that LPLND may effectively treat nonenlarged metastatic LPLNs.…”
Section: Introductionmentioning
confidence: 99%
“…Although local recurrence rates have decreased & disease-free survival has increased over past 20 years, therapy of rectal cancer has changed (2). Treatment of locally advanced rectal cancer presents difficulties for both clinicians & studied cases in terms of influence on long-term functional & cancer-specific outcomes as well as degree of aggressiveness of treatment (3). usual therapies for advanced low-rectal cancer to lessen local recurrence have been preoperative chemoradiotherapy & total mesorectal excision.…”
Section: Introductionmentioning
confidence: 99%